Vitamin D3 Inhibits Helicobacter pylori Infection by Activating the VitD3/VDR-CAMP Pathway in Mice - Zhou, Anni; Li, Lei; Zhao, Guiping; Min, Li; Liu, Si; Zhu, Shengtao; Guo, Qingdong; Liu, Chunjie; Zhang, Shutian; Li, Peng (Frontiers in Cellular and Infection Microbiology, 2020)
Helicobacter pylori (H. pylori) infection is closely associated with the occurrence and development of gastric diseases. Therefore, eliminating H. pylori infection should help to prevent gastric diseases. Vitamin D3 (VitD3, 1,25(OH)2D3) was previously observed to exhibit anti-H. pylori infection activity in clinic, but these results were reported in heterogeneous in vivo studies without elucidation of the underlying mechanisms. In the present study, we established H. pylori infection models in both wild-type and VDR knockdown (VDR-KD) mice, which were used to demonstrate that VitD3 inhibits H. pylori infection by enhancing the expression of VitD receptor (VDR) and cathelicidin antimicrobial peptide (CAMP). Furthermore, VDR-KD mice that exhibited lower VDR expression were more susceptible to H. pylori infection. In cultured mouse primary gastric epithelial cells, we further demonstrated that the VitD3/VDR complex binds to the CAMP promoter region to increase its expression. These data provide a mechanistic explanation of the anti-H. pylori infection activity of VitD3 at the molecular level in mice and suggest a new avenue for the clinical management of H. pylori eradication therapy.